Evolution law of overlying rock fracture field in goaf mining with double-roof-cutting retaining roadway - Xiaobo Lv; Shengyong Hu; Jun Nian; Chunsheng Deng; Bo Zhao; Cheng He; Yansheng Wang; Xitu Zhang; Wei Zhang (Scientific Reports)
Abstract This study comprehensively combines physical analog modeling, numerical simulation, on-site monitoring, and other methods to explore the overburden rock fissure development characteristics under double-roof-cutting (DRC) with retained roadway conditions. The analysis of performed tests, simulations, and on-site monitoring proves that under the above mining conditions, the stress transfer between the roof plates of the open area and the roadway on both sides of the cut top is interrupted, the overburden load being retained in the middle of the open area. The stress in the middle of the open area of the former is increased by 5% compared with that of the latter, with a higher degree of stress increase. The amount of overburden rock subsidence in the open area of the former is reduced by 45–80% compared with the latter. Under DRC, heights of the overlying rock collapse and fissure zones are 18 m and 40 m, respectively, versus 15 m and 46 m of those without roof-cutting. Fissures in both zones are the most developed, turning into gas transportation channels. This study findings provide theoretical basis for exploring the gas transportation patterns in double-cutting top tunnels.